Perancangan Alat Bantu Proses Penyablonan yang Ergonomis - Mauluddin, Yusuf; Ariyana, Resha (Institut Teknologi Garut, 2025)
Mutbiea is one of the screen printing shops where the process is completed in a standing position. Screen printing in a standing position can cause soreness in several parts of the body. The soreness is felt in the neck, back, hands, and feet. Improvements that can be made to reduce soreness due to standing are to evaluate posture using the REBA (Rapid Entire Body Assessment) method. Based on the REBA calculation to reduce the risk of posture, a tool design is carried out using the NIDA (Need, Idea, Decision, and Action) method. In the NIDA method, the use of EFD (Ergonomic Function Deployment) can be used to determine the need for ergonomic tools. Based on the results of the study, it can be concluded that the tools for the printing process need to be redesigned. This is because the splicing activity carried out by four operators has a REBA score between 5-7 with a moderate risk level so that the operator's posture needs to be explored further so that changes can be made immediately. Meanwhile, for the drying activity, three operators have a score of 5-7 with a moderate risk level and one operator with a score of 3 has a slight risk. After designing a new screen printing tool, the risk level of posture using RULA has decreased to 3 with a low risk level.